2016
DOI: 10.3390/ijms17122010
|View full text |Cite
|
Sign up to set email alerts
|

The Large Phenotypic Spectrum of Fabry Disease Requires Graduated Diagnosis and Personalized Therapy: A Meta-Analysis Can Help to Differentiate Missense Mutations

Abstract: Fabry disease is caused by mutations in the GLA gene and is characterized by a large genotypic and phenotypic spectrum. Missense mutations pose a special problem for graduating diagnosis and choosing a cost-effective therapy. Some mutants retain enzymatic activity, but are less stable than the wild type protein. These mutants can be stabilized by small molecules which are defined as pharmacological chaperones. The first chaperone to reach clinical trial is 1-deoxygalactonojirimycin, but others have been tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…However, since a higher DGJ concentration was used in combination with a shortened incubation period of 60 h in our in-house assay as compared to the GLP-validated study, one could speculate that this difference has a significant systematic impact on the reproducibility of the results. Nevertheless, it was impressively shown that even data from different cell systems (COS-7 vs. HEK293 cells) correlate very well as long as they were obtained from in vitro overexpression systems [15]. It was also reported that there was a discrepancy of 10.5% in the amenability classification [16] between a pre-GLP HEK assay developed in clinical phase II [21] and the GLP-validated study [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since a higher DGJ concentration was used in combination with a shortened incubation period of 60 h in our in-house assay as compared to the GLP-validated study, one could speculate that this difference has a significant systematic impact on the reproducibility of the results. Nevertheless, it was impressively shown that even data from different cell systems (COS-7 vs. HEK293 cells) correlate very well as long as they were obtained from in vitro overexpression systems [15]. It was also reported that there was a discrepancy of 10.5% in the amenability classification [16] between a pre-GLP HEK assay developed in clinical phase II [21] and the GLP-validated study [14].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies concerned the assessment of variant α-Gal A enzyme activity in different cell culture systems. It was found that inter-assay discrepancies in residual activity and DGJ responsivity of the variants persist [15]. During the clinical phase 3 study, a standardized good laboratory practice (GLP)-validated human embryonic kidney cell-based in vitro assay was established to identify DGJ amenability of GLA gene variants [14], and it is currently the only approved method for this assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme cleaves globotriaosylceramide, generating galactose that is a product and a reversible inhibitor of the enzyme. There exist more than 400 pathological missense mutations, the majority of which reduce the stability of the protein but do not affect the active site [31,32]. In 1995, some years before Morello et al had coined the term "pharmacological chaperone," Okumya et al [33] showed that galactose stabilizes missense mutants of alpha-galactosidase.…”
Section: Pharmacological Chaperones: the Quick Path To Success Is Notmentioning
confidence: 99%
“…Preventing accumulation and/ or clearance of GL3 leads to the preservation and recovery of cardiac and other organ functions. 8) A limitation of ERT in older patients in an advanced stage was demonstrated in a report, 9) although the definite age and disease stage at which ERT should not be indicated or continued have not been decided yet. 13) In addition, the appropriate age to start ERT for heterozygote patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Additionally, the broad phenotypic spectrum among patients with missense mutations makes it difficult to evaluate the efficacy of ERT. 9,10) We report here the clinical effects of long-term ERT in three patients with the same missense mutation.…”
mentioning
confidence: 95%